EVALUATION OF THE SUCCESS OF THE VEHICLE ADMINISTRATION SYSTEM AND ONLINE TAX (SAKPOLE) WITH MODEL DELONE & MCLEAN (Study of success SAKPOLE according to the Central Java provincial Motor vehicle taxpayers) - Musyafa Al Farizi; Ardian Widiarto; Alvianita Gunawan Putri; Septian Yudha Kusuma; Mella Katrina Sari (Universitas Muhammadiyah Malang, 2020)
This research aims to evaluate the success of the Online Tax Vehicle Administration System (SAKPOLE) with the model approach DeLone and McLean. The analysis method used to test the relationship between variables is the analysis path and analysis tool Amos 22.0. In this study the population was taxpayers of vehicles throughout the province of Central Java. While sampling using purposive sampling methods as well as in collecting data with the error Slovin formula 5% data is obtained and can be processed as much as 360 samples.Based on the results of the analysis obtained the conclusion that only the quality of information and services effect positive and significant against the use of the SAKPOLE system. The quality of information and services of SAKPOLE have a positive and significant impact on the taxpayer satisfaction while the quality of the system is not. In addition, the use of SAKPOLE has positive and significant effect on taxpayer satisfaction. And there is a reciprocal relationship between the satisfaction and the use of SAKPOLE against taxpayers ' benefits